Invisible Dress: Weaving a Theology of Fashion - Ambrosio, Alberto Fabio (Religions, 2019)
This article establishes the framework for a (Christian) theology of fashion, the development of which comes under a research project set up between Luxembourg (Luxembourg School of Religion & Society) and Paris (Collège des Bernardins). The text is structured around three areas: the first reveals how theology can accommodate in its field of thought both the idea of dress (also viewed in terms of its materiality) and the way in which modern society experiments with it: fashion. For as much as theological discourse, particularly Christian, might have shown itself to be critical regarding modern day fashion, it has nevertheless failed to come up with any real theological reflection on the subject. The second area aims to explore responsible ethics for fashion. Often moralising, the attitude of Christian theology needs to give way to an ethical and-vitally-ecological analysis of the effects of fashion in today's world. Clothing might still cover people's bodies, but the issue is not restricted to an individual moral point of view, and extends to the social rules of an ethic that is also one of environmental responsibility. Finally, the totally new perspective that I adopt for outlining these areas requires the aesthetics of dress and fashion to be addressed from a theological point of view. For all its rich history, theological aesthetics has hardly ever concerned itself with developing an aesthetic discourse for dress and fashion, other than for liturgical and religious attire. Once these three new research perspectives have been discussed, I want to outline another field of study, in itself extremely fertile: a treasure trove of metaphors and analogies that would be very useful in theological thinking, adding to its inventory terms originating in the uncovering and stripping away of old ways of thinking that no longer convey in contemporary language the mystery that it is meant to clothe.